2022
DOI: 10.1007/s12079-022-00673-3
|View full text |Cite
|
Sign up to set email alerts
|

Integrin α11β1 in tumor fibrosis: more than just another cancer-associated fibroblast biomarker?

Abstract: There is currently an increased interest in understanding the role of the tumor microenvironment (TME) in tumor growth and progression. In this context the role of integrins in cancer-associated fibroblasts (CAFs) will need to be carefully re-evaluated. Fibroblast-derived cells are not only in the focus in tumors, but also in tissue fibrosis as well as in inflammatory conditions. The recent transcriptional profiling of what has been called “the pan-fibroblast cell lineage” in mouse and human tissues has identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…Substantial evidence has been gathered to demonstrate the relevance of α11β1 signaling in CAFs in distinct solid cancer types, as well as in myofibroblasts during wound healing [reviewed in ( 4 , 11 )]. Here, we report our novel findings on the notable upregulation of integrin α11 expression in the stromal compartment of human and mouse cSCCs, as well as the significant impairment of DMBA/TPA-induced skin tumor growth in mice, accompanied by interesting alterations in the tumor stroma, in the absence of α11 integrin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial evidence has been gathered to demonstrate the relevance of α11β1 signaling in CAFs in distinct solid cancer types, as well as in myofibroblasts during wound healing [reviewed in ( 4 , 11 )]. Here, we report our novel findings on the notable upregulation of integrin α11 expression in the stromal compartment of human and mouse cSCCs, as well as the significant impairment of DMBA/TPA-induced skin tumor growth in mice, accompanied by interesting alterations in the tumor stroma, in the absence of α11 integrin.…”
Section: Discussionmentioning
confidence: 99%
“…The non-vascular, non-inflammatory stromal cells within the TME are designated cancer-associated fibroblasts (CAFs) (3). Recent single-cell RNA sequencing (scRNA-seq), proteomics and flow cytometry approaches have revealed extraordinary heterogeneity and plasticity among CAFs subpopulations (2)(3)(4). The three major subtypes of CAFs, originally identified in pancreatic adenocarcinoma (PDAC), are myofibroblastic CAFs (myCAFs), inflammatory CAFs (iCAFs), and antigen-presenting CAFs (apCAFs) (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DDR2 has also been shown to control the activation of collagen‐binding integrins. Sydecans, additional non‐integrin receptors, have been reported on CAFs and are often related to TGF‐β signaling (particularly Syndecan‐2), but remain an understudied area of CAF mechanobiology (Zeltz et al., 2022).…”
Section: Mechanisms Of Caf Activationmentioning
confidence: 99%
“…Additionally, our previous studies have demonstrated that the crosstalk between CAFs and tumor cells can promote tumor growth and metastasis. , All these functions contribute to tumor growth, invasion, and metastases, which indicate the potential of CAFs’ functions reversing to overcome stromal barriers. Interestingly, integrins, as cell adhesion receptors, have attracted significant attention owing to their roles in desmoplasia and matrix remodeling. , They are heterodimeric transmembrane receptors composed of α and β subunits, the latter of which are verified to be crucial for cell-to-ECM and cell-to-cell interaction. Specifically, integrin β1 (ITGB1) in TME forms specific receptors for fibronectin, laminin, or collagen. Also, ITGB1 participates in CAFs self-renewal and their expression of α-smooth muscle actin (α-SMA, ACTA2) and COL1A1, thus regulating the synthesis of ECM. These findings indicate the significant importance of ITGB1 as a target to regulate the CAFs’ functions for remodeling ECM.…”
mentioning
confidence: 99%